Description of Antonio Lauro's Classical Guitar Playing Technique: Vals Venezolano No. 2 - Waruwu, Dian Kurnia Cristin; Tulus Handra Kadir (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2023)
This study aims to determine the characteristics and techniques contained in the song Vals Venezolano. No. 2 Antonio Lauro's work on classical guitar by Ana Vidovic in a 2015 video performance at the Asamsaal building in Ettlingen, Germany. Tavi jinariu, on Elite Guitarist Youtube account in 2018. This research is descriptive with a qualitative approach, in this case it will describe, describe and describe the characteristics and techniques and training methods to be able to master the technique. The object of research became the center of attention and the target of research was the classical guitar playing technique in Vals Venezolano No. 2 by Antonio Lauro. This research instrument is the researcher himself with the help of several tools to process data such as audio and audio visual recording devices, recording sheets and interview guidelines. This type of data uses primary data taken from Antonio Lauro's Vals Venezolano No. 2 score and secondary data taken from video recordings from Youtube, books or literature and interviews with experts. The step in analyzing the data is the acquisition of interviews from sources, observation and documentation. The results showed that the techniques used in Antonio Lauro's classical guitar: Vals Venezolano No. 2 were apoyando, tirando, harmonic, barre, slur. The characteristics in this song are rubato, syncopation, hemiola, con grazia and waltz. In a special game technique, Ana Vidovic added a 3-string harmonic to fret 12 as a closing style of Ana Vidovic personally that was not listed on the score.